"Men Feel Swell in…"1 Men's Underwear: Functional Necessities or Desirable Luxuries?. Issue 2 (4th May 2018) - Cole, Shaun
Abstract: This article will consider how men's underwear garments, that have been considered a functional necessity from the end of the nineteenth century, have become associated with desirable luxury. It will address the ways in which predominantly invisible, inconspicuous male underwear garments, manufactured by traditional companies with a sense of their own heritage and using high-quality materials (such as Sunspel, Zimmerli, and Schiesser) become a form of luxury. Using Sunspel as a key case study, it will examine such how "heritage" underwear companies produce and promote a luxury product based on their longevity and continued use of quality materials. It will also consider how luxury is evident in contemporary men's underwear, through innovation and development in styles and fabric production and how notions of fit and comfort add to the sense of luxury in the production and consumption of such garments.